Perancangan Sistem Informasi Kasir Toko Retail Berbasis Web Menggunakan Metode Pos (Point Of Sales) - El Vionna Laellyn Nurul Fatich; Asni Tafrikhatin; Yulia Bherlinda; Ariesta Tegar Juangera Reformadyananda (Politeknik Piksi Ganesha Indonesia, 2023)
In carrying out business activities, Toko Tujuh uses manual recording for both sales and purchase transactions. This is less effective and efficient because store management will become more complex when the goods are more complete and plentiful. To overcome this problem is to create a web-based retail store cashier information system. This information system design process uses the Point of Sales (POS) concept which focuses on sales and systems that support the transaction process. Software development uses the Waterfall Method which consists of 5 stages, namely analysis, design, implementation, testing and maintenance. Features such as stock management, sales and purchase transactions and sales and purchase reports will be contained in the information system. With Black Box Testing, test results are obtained that show the information system is valid and suitable for use.